Electronic structures and anisotropic carrier mobilities of monolayer ternary metal iodides MLaI5 (M=Mg, Ca, Sr, Ba). (5th July 2021) - Xin, Baojuan; Hu, Yaoqiao; Wu, Maokun; Cui, Jintao; Li, Luyan; Cheng, Yahui; Liu, Hui; Lu, Feng; Cho, Kyeongjae; Wang, Wei-Hua
Abstract: Exploiting two-dimensional (2D) materials with natural band gaps and anisotropic quasi-one-dimensional (quasi-1D) carrier transport character is essential in high-performance nanoscale transistors and photodetectors. Herein, the stabilities, electronic structures and carrier mobilities of 2D monolayer ternary metal iodides MLaI5 (M = Mg, Ca, Sr, Ba) have been explored by utilizing first-principles calculations combined with numerical calculations. It is found that exfoliating MLaI5 monolayers are feasible owing to low cleavage energy of 0.19–0.21 J m −2 and MLaI5 monolayers are thermodynamically stable based on phonon spectra. MLaI5 monolayers are semiconductors with band gaps ranging from 2.08 eV for MgLaI5 to 2.51 eV for BaLaI5 . The carrier mobility is reasonably examined considering both acoustic deformation potential scattering and polar optical phonon scattering mechanisms. All MLaI5 monolayers demonstrate superior anisotropic and quasi-1D carrier transport character due to the striped structures. In particular, the anisotropic ratios of electron and hole mobilities along different directions reach hundreds and tens for MLaI5 monolayers, respectively. Thus, the effective electron–hole spatial separation could be actually achieved. Moreover, the absolute locations of band edges of MLaI5 monolayers have been aligned. These results would provide fundamental insights for MLaI5 monolayers applying in nano-electronic and optoelectronic devices.